Lymphangitic Pulmonary Metastases in Castrate-Resistant Prostate Adenocarcinoma - Andrew Meyer; Rachel Angelica Mariani; Chadi Nabhan (Case Reports in Medicine)
A 63-year-old man with castrate-resistant metastatic prostate adenocarcinoma with known osseous and pelvic nodal involvement presented with progressive dyspnea for one week. Complete cardiopulmonary evaluation revealed a restrictive lung defect that could not be attributed to any of his previous therapies. On presentation, physical examination revealed coarse breath sounds diffusely with hypoxemia. Computed tomography of the chest showed severe bilateral airspace opacities and ground-glass appearance most consistent with interstitial pneumonitis. The patient was intubated due to progressive hypoxemia and worsening respiratory status despite empiric antibiotics and high dose steroids. Subsequent emergent bronchoscopy with transbronchial biopsies revealed atypical intralymphatic cells that stained positively for prostate-specific antigen and prostatic-specific acid phosphatase, confirming the diagnosis of intralymphatic pulmonary metastasis from prostate adenocarcinoma. Lymphangitic pulmonary metastasis from prostate adenocarcinoma is exceedingly rare, with few reported cases that are biopsy-proven. Herein, we describe a rare case of biopsy-proven lymphangitic pulmonary metastasis in the setting of castrate-resistant prostate adenocarcinoma and provide a comprehensive literature review.